Non-technical skills evaluation in the critical care air ambulance environment: introduction of an adapted rating instrument - an observational study. Issue 1 (December 2016) - Myers, Julia; Powell, David; Psirides, Alex; Hathaway, Karyn; Aldington, Sarah; Haney, Michael
Abstract Background In the isolated and dynamic health-care setting of critical care air ambulance transport, the quality of clinical care is strongly influenced by non-technical skills such as anticipating, recognising and understanding, decision making, and teamwork. However there are no published reports identifying or applying a non-technical skills framework specific to an intensive care air ambulance setting. The objective of this study was to adapt and evaluate a non-technical skills rating framework for the air ambulance clinical environment. Methods In the first phase of the project the anaesthetists' non-technical skills (ANTS) framework was adapted to the air ambulance setting, using data collected directly from clinician groups, published literature, and field observation. In the second phase experienced and inexperienced inter-hospital transport clinicians completed a simulated critical care air transport scenario, and their non-technical skills performance was independently rated by two blinded assessors. Observed and self-rated general clinical performance ratings were also collected. Rank-based statistical tests were used to examine differences in the performance of experienced and inexperienced clinicians, and relationships between different assessment approaches and assessors. Results The framework developed during phase one was referred to as an aeromedical non-technical skills framework, or AeroNOTS. During phase two 16 physicians from speciality training programmes in intensive care, emergency medicine and anaesthesia took part in the clinical simulation study. Clinicians with inter-hospital transport experience performed more highly than those without experience, according to both AeroNOTS non-technical skills ratings (p  = 0.001) and general performance ratings (p  = 0.003). Self-ratings did not distinguish experienced from inexperienced transport clinicians (p  = 0.32) and were not strongly associated with either observed general performance (r s  = 0.4, p  = 0.11) or observed non-technical skills performance (r s  = 0.4, p  = 0.1). Discussion This study describes a framework which characterises the non-technical skills required by critical care air ambulance clinicians, and distinguishes higher and lower levels of performance. Conclusion The AeroNOTS framework could be used to facilitate education and training in non-technical skills for air ambulance clinicians, and further evaluation of this rating system is merited.